Effect of a Self-Management Program based on 5A Model on Dyspnea and Fatigue Severity among Patients with Chronic Obstructive Pulmonary Disease: a Randomized Clinical Trial - Maryam Heidari; Sadigheh Fayazi; Hamid Borsi; Khadijeh Moradbeigi; Neda Akbari Nassaji (Tehran University of Medical Sciences, 2015)
Background & Aim: Exacerbation of the symptoms among patients with chronic obstructive pulmonary disease is a part of the disease's cycle . Despite having medical treatments, most patients experience severe degrees of dyspnea. Self-management programs can help relieving the symptoms. T his study aimed to assess the effect of a self-management program on dyspnea and fatigue severity in patients with chronic obstructive pulmonary disease (COPD) .   Methods & Materials: In this randomized clinical trial, 50 patients with COPD referred to Apadana clinic in Ahvaz were recruited into the study. Patients were randomly allocated to control and intervention groups. The intervention group received a self-management program designed based on the 5A model; the control group did not receive any intervention. Patients were assessed using the Fatigue Severity Scale and the Borg Dyspnea Scale at baseline and three month later. The Chi-squared test and t-test were used to analyze the data .   Results: There was no significant difference between the two groups in fatigue severity at baseline. At the end of the three months, the fatigue severity score differed significantly between the two groups (P=0.004). There was also significant reduction in the patients' dyspnea in the intervention group than the control group after 12 weeks (P<0.001) .   Conclusion: Our program was effective in reducing the COPD symptoms among patients. This simple and non-expensive program can be applied as a beneficial intervention to decline major difficulties of the disease among patients with COPD .